Effectiveness of mindfulness-based interventions on empathy: A meta-analysis - Hu, Zhengyu; Wen, Yurong; Wang, Yafei; Lin, Yangyang; Shi, Jian; Yu, Zihan; Lin, Youtian; Wang, Yuling (Frontiers in Psychology, 2022)
Empathy is essential for human survival and social interaction. Although mindfulness-based interventions (MBIs) have been used to improve empathy in healthy populations, its therapeutic efficacy remains unknown. This study aims to investigate the therapeutic effects of MBIs on empathy in a healthy population and the potential factors affecting the efficacy of MBIs. The literature search focused on PubMed, Embase, Web of Science, Cochrane Library, and CNKI from inception to September 2022. Randomized controlled trials and quasi-experimental studies reporting the effects of using MBIs on empathy in healthy populations were included. A total of 13 studies were included in this review. Results of the meta-analysis showed that MBIs improved empathy (SMD, 0.372, 95% CI, 0.164–0.579, p = 0.001) in the healthy population compared with that in the control group. Moreover, results of the subgroup analysis showed that intervention dose (over 24 hours versus under 24 hours), format (online versus offline), and types (different types) were important factors affecting treatment outcomes. This comprehensive review suggests that MBIs are effective treatment for empathy in healthy population. Future research should markedly focus on large-sample, rigorously designed experiments to explore the long-term effects of MBIs on empathy and to elucidate the underlying mechanisms of MBIs. This study provides a reference for the daily application of MBIs.